A three-dimensional dynamic model for train-track interactions - Xu, Lei; Zhai, Wanming (Applied Mathematical Modelling, 2019)
•A 3-D train-track interaction model is developed with wheel-rail rigid-contact hypothesis.•The train-track coupling matrices with characterization of wheel-rail separations are illustrated.•An extended method for infinite length computation is proposed.•Model validations and numerical examples are presented. This paper develops a novel three-dimensional (3-D) train-track interaction model, where the train is modelled as a group of multi-rigid-body vehicles connected by coupler and gear draft systems, and the tracks are modelled as ballastless tracks using finite element method, and finally the train and the tracks are integrated into an entire system by train-rail coupling matrices. In this model, the time-dependent coupling matrices are developed to characterize the train-track interaction in 3-D space. Mostly important the difficulties in establishing dynamic equations of motion for train-track systems by matrix representations of wheel-rail separation and infinite length computation are properly solved. The numerical results show that this model has high efficiency, stability and accuracy in the calculation of train-track interactions. Besides this model can further provide insights into a number of railway dynamics related subjects, such as train-track dynamic assessment and train derailment.